PROSES PENGOLAHAN LOGAM BERAT KHROM PADA LIMBAH CAIR PENYAMAKAN KULIT DENGAN EPS TERIMOBILISASI - Nia Anisti Rahmahida; Zainus Salimin; Junaidi Junaidi (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
ABSTRACTLeather tanning industryproduced waste water contained of heavy metal Chrom that can be dangerous for the environment. One of the methods to remove Cr in wastewater was used Extracellular Polymeric Substances (EPS) that extracted from the activated sludge. This research was done with used EPS that immobilized in epoxy resin as adsorbent and used artificial waste water with concentration of 15,9 ppm. This research was done in continuous and recirculation process with variable of pH 5, 6, 7 and the flows were 3, 5, 7 ml/min. The result showed that the best adsorption happened in pH 5, the flowwere 3 ml/minwith the adsorption capacity was 6,382 mg/g EPS-epoxy and the removal efficiency was 89,2 %